2022
DOI: 10.15244/pjoes/148065
|View full text |Cite
|
Sign up to set email alerts
|

A Pre- to Post-COVID-19 Change of Air Quality Patterns in Anhui Province Using Path Analysis and Regression

Abstract: During the epidemic period, primary emissions across the world were significantly reduced, while the response to secondary pollution such as ozone differed from region to region. To study the impact of the strict control measures of the new COVID-19 epidemic on the air quality of Anhui in early 2020, the air quality monitoring data of Anhui, from 2019 to 2021, specifically 1 January to 30 August, was examined to analyze the characteristics of the temporal and spatial distribution. Regression and path analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…6 and 7, S1-4 ). These findings agreed well with the prior studies documented by Hasnain et al (2021) and Bhatti et al (2022) . Compared with the air quality status of Jiangsu Province, the reductions in the concentrations of different air pollutants in Anhui were relatively lower during the first phase ( Table S1 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…6 and 7, S1-4 ). These findings agreed well with the prior studies documented by Hasnain et al (2021) and Bhatti et al (2022) . Compared with the air quality status of Jiangsu Province, the reductions in the concentrations of different air pollutants in Anhui were relatively lower during the first phase ( Table S1 ).…”
Section: Resultssupporting
confidence: 93%
“…The reduction ratio for PM 2.5 concentration was greater than other pollutants, while PM 10 , SO 2 and NO 2 indicated relatively similar tendencies with some fluctuations in Zhejiang. Past studies also reported that except for O 3 , the concentrations of different air pollutants were decreased during the COVID-19 control period compared with the prior years in different areas and regions across China ( Chen et al, 2020 ; Zhao et al, 2020a ; Hasnain et al, 2021 ; Bhatti et al, 2022 ).…”
Section: Resultsmentioning
confidence: 91%
“…On the contrary, infrared images can highlight thermal targets in low light or severe weather and contain little texture information because of their low spatial resolution. Infrared and visible image fusion can integrate the complementary virtues from infrared and visible images into synthetic images, which not only conform to human visual perception but also adapt to the application in various vision systems ( Bhatti et al., 2022a ; Bhatti et al., 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, during the COVID-19 pandemic lockdown period, a sharp drop in air pollution was noticed in several areas and regions all around the world shown by satellite images (Holcombe and O'Key 2020). The lockdown is vital to the public health response to COVID-19, and it has also brought unexpected benefits for the environment (Abdullah et al, 2020;Bhatti et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%